Effect of intensive nutrition education and counseling on hemoglobin level of pregnant women in East Shoa zone, Ethiopia: randomized controlled trial - Ermias Bekele Wakwoya; Tefera Belachew; Tsinuel Girma (BMC, 2023)
Abstract Background The aim of this study was to assess the effect of intensive nutrition education and counseling on hemoglobin level during pregnancy. Methods and materials The study was a one year two-arm parallel design cluster randomized controlled trial in East Shoa zone, Ethiopia. End-line data were collected from 163 intervention and 163 control group pregnant women. The intervention was a three consecutive trimester based counseling sessions using health belief model, weekly regular SMS sent on mobile phone containing core message and providing leaflet with food menu of Iron rich diet. The women in the control group received routine nutrition education from facilities. After adjusting for potential confounders, a linear mixed-effects model was used to assess the intervention effect. Results There was a significant change in both hemoglobin level and proportion of anemia in the intervention group. The mean hemoglobin level within intervention group before and after intervention was (12.08± 1.15, 12.53± 1.18) with p value of 0.01. The prevalence of anemia among intervention group declined from 14.7 % at the baseline to 9.2% after intervention. At the end of the trial, women in the intervention group had significantly better hemoglobin level than women in the control group (β = 0.50, p < 0.01). Conclusion The intervention was effective in improving the hemoglobin level and consumption of iron rich diet among pregnant women. Therefore, employing trimester based counseling by using HBM constructs and regular reminding messages have to be provided to pregnant women as part of the regular antenatal care service.